Floristic composition of mangrove community in Ngurah Rai Forest Park and Nusa Lembongan, Bali, Indonesia - I MADE, SAKA WIJAYA; I PUTU, SUGIANA; Ida Ayu, Astarini; I KETUT, GINANTRA; Khairul Adha, A. Rahim (Universitas Sebelas Maret, Surakarta, Indonesia, 2024)
Wijaya IMS, Sugiana IP, Astarini IA, Ginantra IK, Rahim KAA. 2024. Floristic composition of mangrove community in Ngurah Rai Forest Park and Nusa Lembongan, Bali - Indonesia. Biodiversitas 25: 300-309. The floristic composition of mangroves can be influenced by various factors, one of which is the size of the island. Ngurah Rai Forest Park is one of the mangrove areas in the mainland of Bali, while Nusa Lembongan on the southeastern mainland represents the mangroves on the small island. This research aimed to study the floristic composition of the mangrove species in these areas based on the diversity and the community structure. A total of 20 true mangrove species were found in these mangrove areas, with 18 species in Ngurah Rai Forest Park and 15 species in Nusa Lembongan. The mangrove community structure comprises Sonneratia alba and Rhizophora (R. apiculata, R. mucronata, and R. stylosa). S. alba has more impact in relative dominancy, while the Rhizophora has more impact in relative density. This study reports moderate diversity based on the Shannon-Wiener Index in both locations in all growth forms (trees, saplings, and seedlings). The Index of Dominance and Index of Evenness indicate the mangrove community is in stable condition with no extremely dominated species and fairly even species distribution. The mangrove condition is categorized as Good with Dense Trees based on the Decree of the Minister of Environment number 201 of 2004.